Strategi Pemasaran Pengusaha Event Organizer Dalam Pariwisata MICE Di Yogyakarta - Yitno Purwoko - MKP UGM Yogyakarta (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2016)
Abstract - Exhibition business grows rapidly in Yogyakarta. This is triggered by increasing business competition among companies, so they need space to market their products. Accessibility, amenity and attractions also trigger the growth of exhibition industry in Yogyakarta, which was awarded with “The Most Popular MICE Destination” by the Ministry of Tourism and Creative Economy. This condition is captured by exhibition businesspeople. In its development, new event organizers emerge to join exhibition business in Yogyakarta, so competition grows among them. Marketing strategy is a tool for businesspeople to market their products to consumers. Marketing strategy has a marketing mix called 7P, which is promotion, product, process, price, place, physical evidence, people. There are only a few studies on marketing strategies of event organizers. This study was aimed to determine the marketing strategy performed by event organizers in Yogyakarta. The method used was qualitative with categorization of themes in 7P dimension in marketing mix. The data collection technique was in-depth interview with event organizers. Data analysis process was performed by collecting data (in-depth interview, observation and documentation). After the data was collection, data reduction and data selection were performed. Then, coding was performed to find keywords and group keywords with the same meanings into certain categories. The next step was combining categories on dimensions of marketing strategy performed by event organizers. This method determined that the marketing mix dimensions used by most event organizers were promotion, place, and product. Several event organizers also added price and people into the marketing mix. Physical evidence dimension wasn’t found in the marketing mix of event organizers. Marketing strategy outside of 7P marketing mix was also found, i.e. cooperation, maintenance customer, and evaluation.Keywords: marketing strategy, event organizer, MICE tourism Abstrak - Penelitian ini mengeksplorasi strategi pemasaran yang diterapkan oleh para pelaku bisnis MICE di Yogyakarta. Eksplorasi dilakukan dengan metode kualitatif. Dengan memahami strategi pemasaran yang selama ini diterapkan oleh para pelaku bisnis EO dalam memasarkan wisata MICE, maka dimungkinkan untuk dilakukannya evaluasi untuk meningkatkan pemasaran wisata MICE sehingga kualitas wisata MICE di Yogyakarta dapat terus meningkat.Penelitian ini merupakan penelitian kualitatif, eknik pengumpulan data yang utama dilakukan melalui wawancara terhadap 7 narasumber dari beberapa perusahaan EO yang berbeda.Penulis menggunakan bauran pemasaran 7p (promotion, place, people, product, price, proses dan physical evidence). Meskipun tidak semua aspek bauran pemasaran sesuai dengan hasil riset, meskipun demikian penelitian ini telah mengungkap berbagai strategi baru dalam pengembangan perusahaan.Kerjasama antar perusahaan dan customer harus dijaga dengan baik, disamping itu penelitian ini juga mengungkapkan seberapa besar kepuasan yang diberikan kepada pengunjung.Saat ini EO perlu melakukan berbagai inovsi dan memunculkan ide-ide kreatif, sehingga kerjasama perusahaan dengan para sponsor juga dianggap sebagai aspek terpenting.Keywords: marketing strategy, event organizer, MICE tourism